Hyperuricemia and Pro Inflammatory Cytokine (IL-1Î², IL-6, and TNF-Î±) - Hadi, Suyanto; Sudarsono, D; Suntoko, Bantar (Indonesian Rheumatology Association, 2010)
Background. Rugerio et al 2006 reported that there were a positive correlation between the level of hyperuricemia and the level of IL-1Î², IL-6, and TNF-Î± pro infl ammatory cytokines value. On the other hand, Choi et al reported a negative correlation between hyperuricemia and the level of pro infl ammatory cytokine in the late phase of hyperuricemia.Methods. Venous blood samples were collected and stored at a temperature of - 80oC from in- and outpatients with hyperuricemia with age of more than 17years old at Dr. Kariadi Hospital, Semarang. The level of uric acids (mg/dl) were examined with enzymatic colorimetric technique (Roche Diagnostics) whereasthe levels of IL-1Î², IL-6, and TNF-Î± pro infl ammatory cytokines (pg/ml) were examined with enzyme linked immunosorbent assay (ELISA) technique using ultrasensitive commercial kit (Human ultra sensitive, Biosource International Inc Europe), and ELX 800, 2002 machine. The normality of the data was tested withOne-Sample Kolmogorov-Smirnov technique and the correlation was tested with Spearman correlation (data with abnormal distribution) or Pearson correlation (datawith normal distribution).Results. There was a weak positive correlation between the level of hyperuricemia and the level of IL-1 Î² cytokine in Spearman correlation test with r value = 0.246 and p value > 0.05 in Spearman correlation test. On the other hand, there was a weak negative correlation between the level of hyperuricemia and the level of TNF-Î± cytokine with r value = - 0.096 and p value > 0.05. There was also weak negative correlation between the level of hyperuricemia and the level of IL-6 cytokine with r value = - 0.072 and p value > 0.05 in Pearson correlation test.Conclusion. There was a weak positive correlation but not sifnificant between the level of hyperuricemia and the level of IL-1Î².